THE EFFECT OF ORGANIZATIONAL CULTURE, MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Ihsani, Nurul; Aris Wijayanto (Dinasti International Journal of Digital Business Management, 2020)
This study aims to identify and explain the effect organizational culture, motivation, and job satisfaction on employee performance in PT Taiyo Sinar Raya Teknik. This study is quantitative. The population of the study was all employees of PT Taiyo Sinar Raya Teknik. It applied a probability random sampling technique involving 120 respondents. The collected data were analyzed with multiple linear regression analysis. The results showed that organizational culture had a positive and significant effect on employee performance; motivation had a positive and significant effect on employee performance; and job satisfaction had a positive and significant effect on employee performance. It indicates that organizational culture, motivation, and job satisfaction simultaneously, positively, and significantly affect employee performance.